How do you factor # 3a^2 - 6ab +2a - 4b#?

1 Answer

Answer:

=#(3a +2)(a -2b)#

Explanation:

When there are 4 or more terms in an expression, group them.
Make sure there is a + sign between the groups.

#3a^2 - 6ab + 2a - 4b " can be grouped as"#:

=#(3a^2 - 6ab) + (2a - 4b) " find a factor in each pair"#

=#3a(a - 2b) + 2(a - 2b) " there is a common bracket"#

=#(a - 2b)(3a + 2)#

OR:
#3a^2 - 6ab + 2a - 4b " can be grouped as"#:

#(3a^2 + 2a) + (- 6ab - 4b)#:

Taking out different factors will still give the same answer as the first method. NOte that the signs in the second term will change.

#(3a^2+2a) + (- 6ab - 4b)#

=#a(3a +2) -2b(3a +2)#

=#(3a +2)(a -2b)#